(untitled) (Journal of Academic Research, 2026)
Many developing cities experience increasing traffic congestion due to rapid urban growth and the absence of integrated transportation planning. This study evaluates the traffic performance of the intersection of Tripoli Street and Imam Sahnoun Street in Ajdabiya City, which represents a vital urban artery and a strategic connection point within the city’s urban fabric. The problem arises from severe congestion and noticeable operational inefficiency, particularly after the closure of nearby intersections such as the Banks Intersection and Entelat Street Intersection. This has resulted in a “traffic congestion transfer” phenomenon, significantly increasing traffic volumes beyond the intersection’s capacity. The study adopts a descriptive-analytical approach based on field traffic surveys and observation of driver behavior during peak hours. The Highway Capacity Manual (HCM) standards were applied to evaluate the Level of Service (LOS). Results indicate that the intersection currently operates at poor service levels (E and F) during peak periods, with high average delay times and long queue lengths, in addition to increased traffic conflict points that elevate accident risks. The study proposes a radical engineering solution involving the replacement of the conventional intersection with a Dual Roundabout system before and after the intersection. A comparative before–after analysis demonstrates that this proposal would significantly improve traffic flow efficiency, enhance the Level of Service to (C or D), and substantially reduce conflict points. Consequently, this solution would improve road safety, reduce accident severity, and pr